Society Differentiation, Can Human Rights be Protected?: Critical Study of the Tribes Castration on Community (Case Study of Laporo Buton) - Birkah Latif; Agung Syaputra; Nurul Zashkia; Rifda Aprilia Rusfayanti (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2019)
In administering a country based on the rule of law, the main element is the enforcement of human rights. In every country still found, there are discriminatory discriminations against citizens, both those that are needed from state actions, and those needed from the community. With the existence of a convention on the protection of special human rights, the state must approve and protect its citizens. Problems that occur in pluralistic Indonesia is in preventing the social life in community. The research method of the paper is an empirical juridical method to answer whether Indonesia handling the enforcement of human rights and review human rights protection in Indonesia when dealing with communities which holding customary law in their community. If the practice of customary law turns out there is discriminatory practices against the tribe or sub-tribe in it, then how does the state uphold human rights?